Semiotics of mathematics problem-solving in Mason’s generalization - Ihda Mutimmatul Fitriyah; Yuni Arrifadah; Siti Lailiyah (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
Semiotics are signs that include codes, symbols, words, icons, objects, or gestures. This descriptive-qualitative study aimed to describe the semiotics of mathematics problem-solving in Mason’s generalization. Generalization is a finding pattern process in which students will use the different strategies with some semiotics. The subjects were three of 30 eleventh graders from a senior high school in Gresik Regency, Indonesia, that were selected using the purposive sampling technique. Data was collected through documentation, written test, and interview. Data was analyzed by reducing data, presenting data, and concluding. The results of this study showed that students could present the semiotics of gesture, word, and symbols in the process of Mason’s generalization, even though in several stages or indicators the students could not present semiotics. The absence of semiotics in several stages or indicators was not because students could not do such things, but because students passed or skipped these stages. In the perception of generality stage, the semiotics of gesture, word, and symbols could emerge simultaneously. However, for expression of generality, symbolic expression of generality, and manipulation of generality stage, students did not present the three semiotics’ components simultaneously.